Infrastructure and Paramedic Competence in Enhancing Community Satisfaction: Implications for Public Health Service at Rumah Tiga Community Health Center, Ambon - Sindy Erawaty Simamora; Normawati Normawati; Hengky Virgo Richardo Pattimukay (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aims to examine whether facilities and infrastructure, as well as the competence of health workers, influence community satisfaction at Puskesmas Rumah Tiga in Ambon City Methodology: The study uses a quantitative explanatory approach. Data were collected through questionnaires distributed to 50 patients who received services at Puskesmas Rumah Tiga during the research period. Respondents were selected using accidental sampling, based on their availability at the time of data collection.The questionnaire measured three variables: facilities and infrastructure, health workers’ competence, and community satisfaction. All items were assessed using a five-point Likert scale. The data were analyzed using multiple linear regression with SPSS to determine both partial and simultaneous effects of the independent variables on community satisfaction. Main Findings: These findings make an important contribution to social science by demonstrating how the quality of physical resources and the competence of health workers shape community perceptions of public services. From a social and policy perspective, the results underscore the need for simultaneous investment in infrastructure and human resource development to enhance health service performance, strengthen public governance, and promote inclusive social development through responsive and citizen-oriented service delivery Novelty/Originality of This Study: This study provides empirical evidence from a primary healthcare center in Ambon City, Maluku Province. Research examining similar variables has mostly been conducted in western Indonesia, particularly in Java and Sumatra. Studies focusing on eastern Indonesian urban contexts remain relatively limited.The findings highlight the importance of improving both service facilities and staff competence to enhance community satisfaction. For local health administrators and policymakers, the results suggest that efforts to strengthen infrastructure should be accompanied by continuous improvement of professional competence among health workers.